Bayesian approach to evaluation of distance courses - Mockus, Jonas; Vinogradova, Irina (Lietuvos matematikos rinkinys, 2014)
Many real applications are using uncertain data This include expert decisions based on their subjective opinions, The uncertainty can be evaluated applying fuzzy sets theory or the methods of mathematical statistics. In this paper it is proposed to use the Bayesian approach by different distribution functions defining the expert opinion and some prior information. The results are illustrated evaluating the quality of distant education courses.